2016
DOI: 10.3847/0004-637x/831/1/63
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Activities of Nearby S0 Galaxies

Abstract: We present a study of nuclear activities in nearby S0 galaxies. After crossmatching the Sloan Digital Sky Survey Data Release 7 (SDSS DR7) with the Third Reference Catalog of Bright Galaxies (RC3) and visually checking the SDSS images, we derive a sample of 583 S0 galaxies with the central spectrophotometric information. In order to separate nebular emission lines from the underlying stellar contribution, we fit the stellar population model to the SDSS spectra of these S0 galaxies. According to the BPT diagram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…Kannappan 2004;Kewley et al 2006a). Xiao et al (2016) find about 8% of an S0 sample exhibits central star formation. They also found that the majority of these SF S0 galaxies have a stellar mass below 10 10.6 M .…”
Section: Star-forming S0smentioning
confidence: 98%
“…Kannappan 2004;Kewley et al 2006a). Xiao et al (2016) find about 8% of an S0 sample exhibits central star formation. They also found that the majority of these SF S0 galaxies have a stellar mass below 10 10.6 M .…”
Section: Star-forming S0smentioning
confidence: 98%
“…The bulge radius coincides with features in the J − K color profiles of NGC 4305,NGC 4497,and NGC 4584. Bulges that are redder than the surrounding disk are a common feature in larger S0s (e.g. Xiao et al 2016). Neglecting the color measurements in the outermost bins, which are susceptible to errors in sky subtraction and noise, then there are systematic J −K gradients in NGC 4305, NGC 4491, and NGC 4584, in the sense that J − K becomes smaller towards larger radii.…”
Section: Isophotal Propertiesmentioning
confidence: 99%
“…we derive logΣ SFR ∼ −0.78 M yr −1 kpc −2 , which is lower than the mean value, −0.48 M yr −1 kpc −2 , of 45 star-forming S0 galaxies with the same method (Xiao et al 2016).…”
Section: Spectral Classificationmentioning
confidence: 58%
“…We obtained that the nebular extinction, A V,nebular , for NGC 3665 is ∼ 1.3, which is larger than the mean value, 1.06 ± 0.66, of 45 star-forming S0 galaxies (Xiao et al 2016) from the Sloan Digital Sky Survey (SDSS; Abazajian et al 2009).…”
Section: Spectral Classificationmentioning
confidence: 71%